Analysis of Human Knowledge About the Spirit Perspective of Q.S Al-Isra' Verse 85 - Al Hidayati; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2024)
The purpose of analyzing the Al-Isra' letter is to find out asbabunnuzul about this letter. In the Qur'an, the meaning of ruh varies greatly depending on the context in which the word al-ruh is used. Believing in the existence of spirits is one of the beliefs taught by the Koran and believing in unseen matters is one of the pillars of religious belief. All religions stand on this belief, with that belief humans can feel peace. Tafsir scholars from the past until now still discuss the meaning and nature of the spirit. Islamic thinkers have long tried to provide various answers. But none of it satisfies reason. Their discussion cannot be considered to deviate from the guidance of this verse because the answer given by the Qur'an above cannot be absolutely understood as the final answer to this question. Thus it can be said that the spirit is still a mystery. This is where this research was conducted to discuss and reveal knowledge about the spirit. Therefore, it is very necessary to understand the spirit in the Qur'an. This research method is qualitative and the analysis technique uses library research. The results of this research are the spirit in the Al-Qur'an, an analysis of Surah Al-Isra' verse 85, that the meaning of spirit in the views of scholars varies, it turns out that after being studied and researched, the spirit has many meanings (not just one meaning). That spirit has the meaning of revelation or the Koran, the angel Gabriel, or life. The meaning of ruh in the Qur'an is based on the proposition of the verses of the Qur'an, surah al-isra'ayat 85, as-syura verse 52. Meanwhile, the explanation of ruh, which means jibril, is in surah an-nahl verse 102, as-syuara verse 193 .